Community, Market and State in Development - Otsuka, K.; Kalirajan, K.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2010)
'How to combine the community, the market, and the state in the total economic system is probably the most important agenda for economists geared towards the reduction of poverty in developing economies'. - Professor Yujiro Hayami This volume brings together leading scholars from all around the world to examine and extend Professor Hayami's development model of 'community, market and state', and to pay tribute to his invaluable contribution to economics. The authors provide new empirical analysis with a clear focus on the role of the community in economic development, and its relations with agricultural markets, industrialization and the government, using primary data from major countries in Asia and Africa. This book is indispensable reading for all interested in development economics, government and market studies and international development studies.
Keywords: International economics; Development economics; International relations; Economic policy; Political science; Political economy; International Economics; Development Economics; International Relations; Economic Policy; Political Science; International Political Economy